2014
DOI: 10.1111/imr.12150
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization for solid organ and hematopoietic stem cell transplantation

Abstract: Desensitization protocols are being used worldwide to enable kidney transplantation across immunologic barriers, i.e. antibody to donor HLA or ABO antigens, which were once thought to be absolute contraindications to transplantation. Desensitization protocols are also being applied to permit transplantation of HLA mismatched hematopoietic stem cells to patients with antibody to donor HLA, to enhance the opportunity for transplantation of non-renal organs, and to treat antibody-mediated rejection. Although dese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 176 publications
(309 reference statements)
1
42
0
Order By: Relevance
“…Therefore, the patient received a highdose i.v.IG (1 g/kg bodyweight) on day +33, followed by extracorporeal DSA elimination using plasmapheresis (exchange of 1, 5 plasma volumes against fresh frozen plasma) on days +34 and +35 (MFI 9538 before the first and MFI 6581 after last plasmapheresis). We observed a transient decrease in the DSA titers after each treatment, which was rapidly followed by a rebound of antibody titers the following day -a well-described phenomenon 2 (Supplementary Table S1). …”
supporting
confidence: 52%
See 1 more Smart Citation
“…Therefore, the patient received a highdose i.v.IG (1 g/kg bodyweight) on day +33, followed by extracorporeal DSA elimination using plasmapheresis (exchange of 1, 5 plasma volumes against fresh frozen plasma) on days +34 and +35 (MFI 9538 before the first and MFI 6581 after last plasmapheresis). We observed a transient decrease in the DSA titers after each treatment, which was rapidly followed by a rebound of antibody titers the following day -a well-described phenomenon 2 (Supplementary Table S1). …”
supporting
confidence: 52%
“…Most prophylactic desensitization protocols used irradiated lymphocyte infusions (DLI) or platelet infusions from the original donor or infusion of surrogate platelets. 2 In our patient, no DLI or donor platelets were available, as this donor was prepared for the second donation. In this special situation, we took advantage of the fact that the haploidentical son carried the same mismatched A2 antigen as the donor (Table 1).…”
mentioning
confidence: 99%
“…9,15,2024 The key requirement appears to be sufficient reduction of DSA to prevent Ab-mediated destruction of donor cells before they can engraft. Among the different desensitization regimens, combinations of PP with rituximab and/or IVIG have been most often used and have demonstrated successful DSA reduction.…”
Section: Discussionmentioning
confidence: 99%
“…9,15,2024 Protocols have included adsorption of Abs on Staphylococcus protein A columns or with donor platelets; treatment with the proteasome inhibitor bortezomib; and various combinations of plasmapheresis (PP) with i.v. Ig (IVIG) and/or the anti-CD20 monoclonal Ab, rituximab (reviewed in Zachary and Leffell 24 ). The majority of these reports have been anecdotal, including from one to four cases, but taken together have indicated that reduction of DSA to low levels can permit successful engraftment.…”
Section: Introductionmentioning
confidence: 99%
“…Many therapies have been utilized to negate the effect of HLA antibodies on the graft due to increased incidence of graft failure in recipients with HLA DSAs. These therapies include TPE, IA, IVIG, tacrolimus, mycophenolate mofetil, rituximab, and bortezomib …”
Section: New Diseases – Category IIImentioning
confidence: 99%